(3GdeLehY GdePgH aj bhGYO GdePgHs - (3UdGM GdOjf Ndjd Hf GdYdGFj GdTGaYjs ((3eMeO Hf eMeO Hf EHQGgje GdHdHjSi GdTgjQ HGHf GdCSfOQi s)
(3ChdgG (B:s
(3GdMeO ddg GdaGJM CHhGH GdeYGQa dWGdHjgG CeG HYO aEf GdYde CTQa GdeWGdH hCYdGgG hdeG cGf Gdabg HgPg GdeQJHI GdTQjaI hcCf ef CMSf eG jYGfjg Gdabjg eYQaI GdbhGYO GdcdjI hGdeYGbO GdeQYjI h s
(3BNQgG (B:s
(3gG BNQ eG jSQ Gddg SHMGfg hJYGdi bGd eUfag aQZJ efg HHJ GdebOS SfI SHY hNeSfj hSHYeGFI hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3ai ChdgG Jedc HGSe ESeGYjd Hf eGVi GdSfLjOi hYh ZjQ eDQNs
(3hJedc GdhGba MSjf Hf Sgd SfI (B1261 (3g` hCMeO Hf GdYLei SfI (B1058 (3g` s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3Gdabg GdTGaYjs